2013
DOI: 10.1002/clen.201300092
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Simazine and Diuron Herbicides under Aerobic and Anoxic Conditions Relevant to Managed Aquifer Recharge of Storm Water

Abstract: The fate of simazine and diuron during natural treatment processes occurring in aquifers during managed aquifer recharge (MAR) was evaluated by batch tests in conditions relevant to MAR using urban storm water. The tests were performed with aquifer sediment and wetland treated storm water under aerobic and anoxic geochemical conditions, with and without a carbon source amendment to assess the degradation of these herbicides. The aerobic conditions were suited for the relatively rapid degradation of the positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Managed aquifer recharge (MAR) is a means of water recycling via aquifers that can be attractive for storage and the aquifer can provide water quality improvements during storage . Water quality improvements include the inactivation of pathogens , a reduction in nutrient concentrations , or degradation of organic chemicals , including personal care products . However, subsurface storage can also have deleterious effects on the quality of groundwater that is available for recovery and reuse, through increases in the concentration of major ions and salinity , metals and metalloids , and hydrogen sulfide .…”
Section: Introductionmentioning
confidence: 99%
“…Managed aquifer recharge (MAR) is a means of water recycling via aquifers that can be attractive for storage and the aquifer can provide water quality improvements during storage . Water quality improvements include the inactivation of pathogens , a reduction in nutrient concentrations , or degradation of organic chemicals , including personal care products . However, subsurface storage can also have deleterious effects on the quality of groundwater that is available for recovery and reuse, through increases in the concentration of major ions and salinity , metals and metalloids , and hydrogen sulfide .…”
Section: Introductionmentioning
confidence: 99%
“…Diuron has a relatively low water solubility of 42 mg dm -3 at 25 °C. It is quite *Correspondence: alapi@chem.u-szeged.hu persistent in soil with a typical half-life of 75.5 days and in water-sediment of 48 days [3]. Based on these data and other investigations [4], it can be concluded that this compound and its metabolites pollute the environment over an extended period of time, by leaching and run-off into ground and surface waters.…”
Section: Introductionmentioning
confidence: 91%
“…Kookana et al [104] reviewed the degradation pathways for three herbicides commonly identified in ASTR (atrazine, simazine and diuron), as they may affect groundwater-dependent ecosystems downstream from MAR. Simazine has been shown to degrade under nitrate-reducing conditions which might occur in an aquifer receiving stormwater [105]. The laboratory study reports half-lives for simazine and diuron of up to 32 days and 92 days, respectively, which would allow sufficient degradation prior to recovery in the ASTR system [105].…”
Section: Trace Organic Chemicalsmentioning
confidence: 97%
“…Whilst there is a long-standing body of research on the biodegradation of pesticides under aerobic conditions in the vadose zone [104], there are relatively few studies on the anaerobic biodegradation of pesticides for Australian aquifers [105]. Kookana et al [104] reviewed the degradation pathways for three herbicides commonly identified in ASTR (atrazine, simazine and diuron), as they may affect groundwater-dependent ecosystems downstream from MAR.…”
Section: Trace Organic Chemicalsmentioning
confidence: 99%